Clean energy - Dell, Ronald (RSC clean technology monographs., 2004)
Clean Energy presents a broad survey of the energy problems facing society over the coming decades and the prospects for their solution. The book emphasizes the importance of developing a strategy for the world's future energy supply. The strategy must take into account: the finite supplies of natural gas and petroleum; the increased consumption of fuel by developing economies; the concern over greenhouse gas emissions; the pollution caused by burning coal (especially coal with a high sulphur content); the difficulties and costs of extracting unconventional fossil fuels; and the technical, sociological and cost barriers that restrict the use of renewable forms of energy. Clean Energy sets the various renewable energies (wind, waves, solar etc) in the context of present and projected world production of energy and its use in the time-frame until 2020 and looks speculatively beyond that. It looks at the possibilities for reducing pollution from fossil fuels and tackles the serious problem of how to store energy, in order to smooth out fluctuations in supply and demand. Clean Energy is well illustrated with diagrams and photographs. It is accessible to anyone who has studied science to A-level and will appeal to anyone with a serious interest in environmental matters, and the interaction between energy usage and the environment.